Analisis Kualitatif Senyawa Parasetamol Pada Sampel Biologis Menggunakan Metode Gas Chromatography - Mass Spectrometry (GC-MS) - Siti Nuriah; Mutia Desvi Putri; Sri Rahayu; Chalisya Vanya Advaita; Lina Nurfadhila; Marsah Rahmawati Utami (Journal of Pharmaceutical and Sciences, 2023)
In this review article, an analysis was carried out regarding the use of the Gas Chromatography - Mass Spectrometry (GC-MS) method in the qualitative analysis of paracetamol compounds in various biological samples such as blood, serum, hair, and urine. Paracetamol is a non-opioid analgesic drug used to relieve mild to moderate pain. The method used in writing this article is a literature study using primary data in the form of national journals from the Google Scholar and Sinta databases. The search was carried out using keywords related to the qualitative analysis of paracetamol compounds using the GC-MS method on biological samples. The purpose of reviewing this article is to compare the treatment and preparation processes of various biological samples used in the qualitative analysis of paracetamol compounds using the Gas Chromatography - Mass Spectrometry (GC-MS) method, such as blood, serum, hair, and urine. The results of the study of several journals showed that there were several biological samples used in the qualitative analysis of paracetamol using the GC-MS method, namely blood, serum, hair and urine. Each biological sample has different preparation and extraction procedures according to the characteristics of the matrix. It can be concluded that of the four samples, hair samples can show positive results in a longer period of time while blood and urine samples can only provide drug information for a few days.